2011
DOI: 10.1037/a0022072
|View full text |Cite
|
Sign up to set email alerts
|

Screening for emotional and behavioral risk among students with limited English proficiency.

Abstract: Students with limited English proficiency (LEP) make up one of the fastest growing segments of the student population; however, LEP status is often related to poor academic and behavioral outcomes. Teacher-reported behavioral rating scales can be informative measurements to screen and identify students at risk for behavioral and emotional problems. Given the focus on early identification and the changing demographics in schools, it is important to research the validity of screening instruments, as well as more… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
44
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(48 citation statements)
references
References 35 publications
3
44
1
Order By: Relevance
“…For example, Canadian children in their first year of school classified as having English as a Second Language (ESL; indicates that the child is not yet proficient in English) were rated lower by teachers across all domains of the Early Development Instrument (EDI), including communication skills, social competence, emotional regulation, and physical health, although individual (e.g., gender) and community (e.g., disadvantage) factors attenuated the strength of these relationships (Guhn, Gadermann, Hertzman, & Zumbo, 2010;Janus & Offord, 2007;Puchala, Vu, & Muhajarine, 2010). Other studies have similarly observed less favorable teacher-ratings of emerging bilinguals on social, emotional, and behavioral dimensions (e.g., Dawson & Williams, 2008;Dowdy et al, 2011;Edl et al, 2008;Han, 2010).…”
mentioning
confidence: 90%
“…For example, Canadian children in their first year of school classified as having English as a Second Language (ESL; indicates that the child is not yet proficient in English) were rated lower by teachers across all domains of the Early Development Instrument (EDI), including communication skills, social competence, emotional regulation, and physical health, although individual (e.g., gender) and community (e.g., disadvantage) factors attenuated the strength of these relationships (Guhn, Gadermann, Hertzman, & Zumbo, 2010;Janus & Offord, 2007;Puchala, Vu, & Muhajarine, 2010). Other studies have similarly observed less favorable teacher-ratings of emerging bilinguals on social, emotional, and behavioral dimensions (e.g., Dawson & Williams, 2008;Dowdy et al, 2011;Edl et al, 2008;Han, 2010).…”
mentioning
confidence: 90%
“…Schools need to address what they have in their power to change. Dounay ( 2008 ) argues that schools should receive funding for students who are older, who want to return and earn their high school diplomas. Schools also need to have alternative ways to demonstrate competency in content areas and have credit recovery choices and options.…”
Section: Preventing Dropping Out Of Schoolmentioning
confidence: 99%
“…Lower levels of English language proficiency affect not only students' academic progress, but also their experience of university life in general. Students with lower levels of English proficiency tend to have more school-related problems, such as attention and learning difficulties (Dowdy, diStefano, Dever, & Chin, 2011), as well as limited desire to seek social interactions (Olivas & Li, 2006).…”
Section: Factors Influencing Educational Adjustmentmentioning
confidence: 99%